Predictors of Adherence to Pre-Exposure Prophylaxis among Female Sex Workers in South-Western Nigeria - Adenike Iyanuoluwa Olugbenga-Bello; Oluwatosin Samson Jegede; Norbertta Ekpen Anegbe; Goodman Olayinka (Journal of Clinical Research In HIV AIDS And Prevention, 2022)
Introduction Pre-exposure prophylaxis (PrEP) is an element of the biomedical interventions of Human Immunodeficiency virus (HIV) prevention. The level of protection is strongly correlated to PrEP drug adherence. In Nigeria, the prevalence of HIV among female sex workers (FSW) is 15.5%. The 2020 integrated biological and behavioral surveillance survey did not report on PrEP adherence among FSW. This study therefore assessed the level of adherence to PrEP and its predictors among FSW in South-Western Nigeria. Methodology This cross-sectional analytical study was conducted in 2021. Study population were brothel-based FSW at Gambari Ogbomoso and Lagos, Nigeria. A total of 156 FSW participated in the study. Data was collected using interviewer-administered semi-structured questionnaire and analyzed using IBM SPSS Version 25. Results One hundred and forty-nine properly completed questionnaires were analyzed. Ninety-nine respondents (66.4%) have been working for more than 5years as a FSW and 65(43.6%) had initiation of sex work before 18 years of age. Respondents’ sexual behavior showed that 55 (36.9%) of total respondents had consistent use of condom. One hundred and thirty-four respondents (89.9%) had good knowledge of PrEP, 97 (65.1%) had good attitude towards PrEP while 111 (74.5%) had good perception of risk of HIV infection. One hundred and thirty-two (88.6%) reported to be taking PrEP and 119 (79.9%) had good adherence to PrEP. Predictors of adherence to PrEP were educational status, age of commencement of sex work and monthly income. It was found that educated sex workers were 2.67 times more likely to adhere to PrEP (OR=2.67, 95% CI=1.280-5.591, p=0.019). Those who commenced sex work after clocking 18 years of age were 75% times less likely to adhere to PrEP (OR=0.251, 95% CI=0.106-0.597, p=0.001) while those with average monthly income more than #10,000 were 1.65 times more likely to adhere to PrEP (OR=1.65, 95% CI=0.674-4.042, p=0.0275. Discussion and Recommendation The level of adherence to PrEP is considerably high and underscores a positive effect of the efforts of the Government of Nigeria in controlling HIV as a threat by 2030. Further studies would be useful to understand the behavioral factors associated with low adherence to PrEP among FSW who have spent more than 5 years in sex work.
Keywords: Adherence